(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Echinococcosis of the heart is rare, accounting for only up to 2.0% of all localizations of this zooanthroponosis [1, 4, 6, 8, 10, 11]. A small number of works on cardiac echinococcosis surgery draws attention [1-3, 10]. The paucity of publications and clinical observations on diagnosis and surgical treatment indicates a lack of awareness of clinicians about diagnostic features and methods of surgical treatment. However, in endemic areas there is a rather "high" frequency of patients with cardiac echinococcosis who need surgical treatment.